Potential using of water-soluble polymer latex modified greener road geopolymeric grouts: Its preparation, characterization and mechanism. (1st March 2021) - Tian, Zhongnan; Liu, Xin; Zhang, Zhengqi; Zhang, Kaiwen; Tang, Xiuming
Highlights: A green road grouting material was prepared at ambient temperature. Provide a pathway to reduce drying shrinkage of geopolymeric grouts. The modification mechanism of silicon-acrylic (SiA) latex contains physical and chemical aspects. Abstract: As a green and carbon-friendly material, road geopolymeric grouts have a great application potential as a replacement of cement-based grouts in road reinforcement, but it still possesses some shortcomings, including high drying shrinkage and poor toughness. In this study, four water-soluble polymer latexes were used to prepare the latex modified geopolymeric grouts (LMGG). Four material composition factors, including mixing ratio of mineral precursors, kinds and contents of alkali activators, water-solid ratios and kinds and contents of polymer latexes, were investigated to discuss the effect of each factor on LMGG paste. Then, the physical properties of LMGG were explored and compared with cement-based grouts. Finally, the Mercury Intrusion Porosimetry (MIP), X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Energy-dispersive Spectrum (EDS) and Fourier transform infrared spectroscopy (FT-IR) were used to explore the pore structure, product phase, micromorphology and functional groups to reveal its modification mechanism. In this study, the effects of compositions (mineral precursors, alkali activators, water and polymer latexes) on LMGG pastes were studied and optimized. Using water glass and KOH as activators can obtain excellent strength and initial fluidity. And the addition of 5 wt% silicon-acrylic (SiA) polymer latex had a positive effect on the strength, shrinkage and pore size distribution, improving 7 d compressive strength by 8.1%, 7 d flexural strength by 19.9%, proportion of gel and medium pores by 28.0%, and reducing the total shrinkage by 63.5%. With the addition of SiA latex, the characterization of hydration and geopolymerization product phases of geopolymeric grouts does not change. The modification mechanism of SiA latex in LMGG system involves physical and chemical modification processes. In physical aspect, the polymeric film can be interweaved and wrapped with the geopolymer products, filling cracks and pores. And in chemical aspect, the active groups of SiA latex reacted with the geopolymer products linking the polymer chains with geopolymer products together.